PEDAGOGICAL ASPECTS OF PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN GRAPHIC DESIGN - Ju Dongting (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2020)
The article is devoted to the matter of improving the psychological and pedagogical features of professional training of future graphic design specialists. Namely, suсh features are considered as providing organizational, pedagogical and psychological support, improving the system of professional training of future graphic designers; determination of forms and approaches to support the process of preparing the future graphic designers for professional activity taking into account the real situation on art labor market. Based on the review of literature sources, the concept of “training” is seen as a process of formation and incipience of professional orientation of a graphic designer, mastering the fundamental knowledge that forms the theoretical basis of the profession, knowledge of special disciplines, practical skills and readiness for future work. It is determined that the professional competence of a graphic designer is the unity of their theoretical knowledge and practical readiness to carry out professional activities. To acquire professional competence, a future graphic designer needs a comprehensive, systematic approach to the design, visual perception and retransmission of certain information of the design object, because these objects, as well as all artworks, bear the imprint of time, the level of technical progress, tastes and demands of society. One of the components of the formation of professional competence of students in teaching graphic design is the algorithm of actions in the creation of design projects. It includes a set of conditions (general, particular and specific). It is important for a future graphic designer to have professional skills that require creative abilities. Such skills can be analytical (analyze, comprehend, find ways to optimally solve the problem, etc.), prognostic (provide a clear idea of the purpose, expected result, etc.), reflective (aimed at understanding and analyzing their own actions, deeds) thought processes; personal communicative qualities (verbal communication skills); nonverbal design thinking, etc. It is noted that in the context of professional training of particular importance is the design and visual competence of future graphic designers, which affect the readiness of the future graphic designer to work. The main components of the educational process (personal-resource, creative-operational, design and engineering) that contribute to the development of project thinking are identified. The specifics of the professional activity of a graphic designer are analyzed. These specifics determine their professional competence, the leading role of communication, the ability to use it in graphic design; ability to correlate art activities with computer graphics; skills of transferring creativity to digital, software and technological components of future work